Conceptualising Intercultural Literacy: Narratives from English Language Teachers - Suharni, Suharni; Saidi, Siti Bahirah binti Saidi; Hussein, Nur Hafezah binti (Jurnal Arbitrer, 2024)
This current study investigates how English language teachers in Indonesian higher educational institutions define and conceptualize intercultural literacy and practice it in their classrooms. Eight ELT practitioners were interviewed through narrative inquiry, and the data was analyzed using thematic analysis to explore their lived conceptualizations. The findings suggest three major themes on intercultural literacy, including conceptualization of intercultural literacy, implementation in professional practice, challenges in fostering intercultural understanding, and strategies to overcome these challenges. Teachers defined intercultural literacy as encompassing cultural understanding, adaptability, comparative analysis, and professional knowledge. They integrated it into their teaching through curriculum design, student-centered methods, and digital tools. This was done by weaving these into the curriculum design and retraining pedagogy with student-centric methods and other digital tools. However, the participants mentioned that they faced some obstacles, including institutional barriers, limited funding, and the difficulties of switching from the traditional to the newest teaching method. These issues were mitigated by professional development, collaboration, and inclusive instructional materials. The current research finding indicates the importance of comprehensive professional development and institutional support for teachers in developing intercultural competence in their students. These findings contribute to intercultural literacy in Indonesia and practical recommendations for improving it within Indonesian higher education. The finding highlights the how to prepare students for a globalized world through intercultural literacy and educator support.